PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP HARGA SAHAM PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hari Gursida (Universitas Pakuan, 2015)
ABSTRACTThis study aimed to analyze the effect of profitability and leverage to the price of property companies in Indonesia Stock Exchange 2011-2015 period. Samples in this study as many as nine companies. Sampling in this study using a purposive sampling. Data were analyzed using multiple linear regression analysis. The results show: Return on Investment is partially significant effect on stock prices. Where the higher the return on investment of a company's share price the company would be higher. Earning per Share significantly influence stock prices. Where the higher a company's earnings per share the company's share price will be higher. Debt to equity ratio and significant negative effect on stock prices. Where the results DER negatively affect the stock price. This suggests that the changes DER information can be obtained from the company's financial statements affect the decision of stock prices in the capital market.In simulation, Return on Investment, Earning Per Share and Debt to Equity Ratio simultaneously or together significantly positive effect on stock prices.Keywords: Profitability, Leverage and Stock Price